Ethyl 1-butyl-2-(2-hydroxy-4-methoxyphenyl)-1H-benzo[d]imidazole-5-carboxylate - Reshma Sathyanarayana (Molbank, 2021)
Ethyl 4-(butylamino)-3-nitrobenzoate upon “one-pot” nitro-reductive cyclization using sodium dithionite and substituted aldehyde in dimethyl sulphoxide affords ethyl 1-butyl-2-(2-hydroxy-4-methoxyphenyl)-1H-benzo[d]imidazole-5-carboxylate in an 87% yield. The structural characterization was determined by Fourier-transfer infrared spectroscopy (FT-IR), Proton nuclear magnetic resonance (1H-NMR) , Carbon-13 nuclear magnetic resonance (13C-NMR), mass spectrometry, Ultraviolet-visible(UV-Vis), photoluminescence (PL), thin-film solid emission spectra, cyclic voltammetry (CV) and thermogravimetric (TGA) analysis. Molecular electrostatic potential (MEP) was studied to determine the reactive sites of the molecule.